2016
DOI: 10.1148/radiol.2015142815
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Diagnostic Accuracy of Supersonic Shear-Wave Elastography for the Assessment of Liver Stiffness and Liver Fibrosis in Children: A Pilot Study of 96 Patients

Abstract: SSWE allows accurate assessment of liver fibrosis, even in children with early stage (F1-F2) disease, and the choice of transducer influences liver stiffness values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
96
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 24 publications
13
96
0
6
Order By: Relevance
“…However, another study didn't find any significant difference between different age groups (p = 0.11) [25] and only a trend to an increase of LSMs with age was found when using the linear transducer (p = 0.05). Technical factors may also affect LSMs, including the transducer used: a significant difference was found for mean elasticity between the linear and convex transducers: 5.96 kPa ± 1.31 and 6.94 kPa ± 1.42, respectively (p = 0.006) [25].…”
Section: Liver Stiffness Estimates In Healthy Controlsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, another study didn't find any significant difference between different age groups (p = 0.11) [25] and only a trend to an increase of LSMs with age was found when using the linear transducer (p = 0.05). Technical factors may also affect LSMs, including the transducer used: a significant difference was found for mean elasticity between the linear and convex transducers: 5.96 kPa ± 1.31 and 6.94 kPa ± 1.42, respectively (p = 0.006) [25].…”
Section: Liver Stiffness Estimates In Healthy Controlsmentioning
confidence: 88%
“…LSMs were found to correlate with children's age (r = 0.429, p = 0.006), and to be significantly higher (6.1 ± 1.1 kPa) in babies older than 60 days (n = 10) than in babies of 60 days or below (5.3 ± 1.0 kPa) (n = 30) (p = 0.026) [73]. However, another study didn't find any significant difference between different age groups (p = 0.11) [25] and only a trend to an increase of LSMs with age was found when using the linear transducer (p = 0.05). Technical factors may also affect LSMs, including the transducer used: a significant difference was found for mean elasticity between the linear and convex transducers: 5.96 kPa ± 1.31 and 6.94 kPa ± 1.42, respectively (p = 0.006) [25].…”
Section: Liver Stiffness Estimates In Healthy Controlsmentioning
confidence: 91%
“…Additionally, apnea might not be obtained in young children. In this regard, Franchi et al's recent results showed that SWE liver measurements in children under FB conditions were feasible and accurate [11].…”
Section: Discussionmentioning
confidence: 99%
“…Elastography, mainly consisting of shear-wave elastography and strain elastography, is reported to be useful for the noninvasive diagnosis of hepatic fibrosis by measuring liver stiffness and has become a hot research topic in recent years [12,13,14,15,16,17,18]. Transient elastography (TE), a shear-wave elastography, is now accepted as a noninvasive and validated method for the detection of significant fibrosis and cirrhosis, a role that has been confirmed by considerable scientific evidence [19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%